A Systematic Review Of Elements In Game-based Arabic Language Learning Framework For Dyslexic Children - Noor Azli Mohamed Masrop; Ghazali Zainuddin; Einannabella Nadzri; Asrina Suriani Md Yunus; Muhammad Sabri Sahrir; Sarifah Nurhanum Syed Sahuri (Universiti Sultan Zainal Abidin, 2024)
Journal of Nusantara Studies (JONUS) Volume 8 No.2 Page (334-353)